Theoretical Aspects of Deindustrialisation in Developed World Economies - Piotr WALĄG (Communications of International Proceedings, 2020)
The effects of deindustrialisation, which became apparent most strongly in the 1970s and 1980s in the United Kingdom and the United States, set strategic trends for the next decades of the world economy. The content of this article deals with selected issues relating to the deindustrialisation process, particularly in the United Kingdom and the United States. This article states that the emergence of deindustrialisation in such economic phenomena as investment, the collapse of old industries, the declining strength of trade unions, the relocation of industries and wage differentials are evidence of painful but desirable adjustments for further economic growth. After presenting a theoretical view of changes in the structure of employment in the economy, the concept of deindustrialisation and its most important determinants, within the framework of selected issues, the problem of the decrease in the share of industry in total employment in the economies of the United States and the United Kingdom is presented, as well as its structural sources, i.e. the centralisation of wage negotiations in the United Kingdom, the British minimum wage policy, the effects of strong trade union traditions in the United Kingdom, the relocation of American companies to foreign economic areas, investment in the United States, the positive dimension of the strong wage differential in the United States.
Keywords: deindustrialisation; employment structure; collapse of industries; change in demand structure; increase in productivity; wage differentiation; relocation of enterprises